Selective optical sensing of copper(II) ions based on a novel cyclobutane-substituted Schiff base ligand embedded in polymer films - Aksuner, Nur; Henden, Emur; Yilmaz, Ibrahim; Cukurovali, Alaadin (Elsevier Science Sa, 2008)
The paper reports on the spectral photophysical characteristics of a novel fluorescent Schiff base ligand 4-(1-phenyl-1-methylcyclobutyl-3-yl)-2-(2-hydroxy-1-naphtylidene)thiazole (LH) in solvents of ethanol (EtOH), tetrahydrofuran (THF). and chloroform (TCM) and in solid matrix of polyvinyl chloride (PVC). The LH dye embedded in plasticized PVC matrix has been used for preparing an optical sensor for Cu(II). The response of the sensor is based on the fluorescence quenching of LH by Cu(II) ions. At pH 6.0, the proposed sensor displays a calibration response for Cu(II) over a wide concentration range of 5.0 x 10(-8) to 1.0 X 10(-4) M. The sensor is fully reversible within the dynamic range and the response time tau(90) is approximately 2.5 min under batch conditions. In addition to its high stability and reproducibility, the sensor shows a high selectivity towards Cu(II) ion with respect to common metal cations. The accuracy of the Cu(II) measurements using the proposed sensor was determined by analyzing standard reference materials Of Surface water and natural water. The sensor was also applied successfully for the determination of copper in green and black tea samples. (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Schiff base; PVC matrix; Fluorescence spectroscopy; Optical sensor; Copper(II)